Antigen delivery format variation and formulation stability through use of a hybrid vector. (11th April 2019) - Beitelshees, Marie; Hill, Andrew; Li, Yi; Chen, Mingfu; Ahmadi, Mahmoud Kamal; Smith, Randall J.; Andreadis, Stelios T.; Rostami, Pooya; Jones, Charles H.; Pfeifer, Blaine A.
Abstract: A hybrid biological-biomaterial antigen delivery vector comprised of a polymeric shell encapsulating an Escherichia coli core was previously developed for in situ antigen production and subsequent delivery. Due to the engineering capacity of the bacterial core, the hybrid vector provides unique opportunities for immunogenicity optimization through varying cellular localization (cytoplasm, periplasm, cellular surface) and type (protein or DNA) of antigen. In this work, three protein-based hybrid vector formats were compared in which the pneumococcal surface protein A (PspA) was localized to the cytoplasm, surface, and periplasmic space of the bacterial core for vaccination against pneumococcal disease. Furthermore, we tested the hybrid vector's capacity as a DNA vaccine against Streptococcus pneumoniae by introducing a plasmid into the bacterial core to facilitate PspA expression in antigen presenting cells (APCs). Through testing these various formulations, we determined that cytoplasmic accumulation of PspA elicited the strongest immune response (antibody production and protection against bacterial challenge) and enabled complete protection at substantially lower doses when compared to vaccination with PspA + adjuvant. We also improved the storage stability of the hybrid vector to retain complete activity after 1 month at 4 °C using an approach in which hybrid vectors suspended in a microbial freeze drying buffer were desiccated. These results demonstrate the flexibility and robustness of the hybrid vector formulation, which has the potential to be a potent vaccine against S. pneumoniae .